2014
DOI: 10.19026/rjaset.7.904
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ginger (<em>Zingiber officinale</em>) Oil Yield from Malaysia in Different Hydrodistillation Physical Parameters via Central Composite Design of Response Surface Methodology (RSM)

Abstract: Response Surface Methodology (RSM) with Central Composite Design face cantered (CCD) is the statistical analysis used for optimization process of ginger oil yield from Malaysia. In this study the three factors predictors (Water volume, extraction time and particle size) and one response criterion (Ginger oil yield) were optimized. The final optimization value for high yield of ginger oil is at water ratio of 2660 mL water to 100 g sample at 23.15 h of hydro distillation using medium size particles of dried gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The total essential oil has obtained 100% desirability of objective proposed ( Figure 6). This result of our research has matched with the reports of other authors about optimization of essential oil yields for other genus ginger (zingiber) in the ginger family (zingiberaceae) [8,7,11,12]. …”
Section: Optimization Of the Total Essential Oil Yield Distillationsupporting
confidence: 92%
See 1 more Smart Citation
“…The total essential oil has obtained 100% desirability of objective proposed ( Figure 6). This result of our research has matched with the reports of other authors about optimization of essential oil yields for other genus ginger (zingiber) in the ginger family (zingiberaceae) [8,7,11,12]. …”
Section: Optimization Of the Total Essential Oil Yield Distillationsupporting
confidence: 92%
“…Ida Hasmita et al have studied particle size and duration on the amount of essential oil obtained [7]. Fhataheya Buang et al reported that the yield of ginger oil was significantly affected by water volume, hydro-distillation time and particle size [8]. Besides that, the total essential oil yield depends on other factors such as: drying method of material, parts of plant for distillation, genus of ginger, environment, and time of stored, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen that the CV in Table 2 was 3.56%, less than 10, which indicated the reproducibility of the model. In addition, the PRESS was 0.20, which was within the acceptable range [32]. The above important parameters proved the suitability of the model.…”
Section: Single Factor Experimentssupporting
confidence: 53%
“…The obtained results indicated that the combination of categorical with numeric factors was adequate and for the recommendation for the optimization of Soxhlet extraction (Ahmad et al 2010). The RSM optimizations applied to the hydrodistillation of essential oil from Pistacia lentiscus L. leaves (Haloui et al 2018), ginger (Zingiber officinale) (Buang et al 2014) and different parts of Java Citronella (Cymbopogon winterianus Jowitt) plant (Timung et al 2016) indicates that time is the factor with the statistically most significant importance. Haloui et al (2018) proved the high efficiency of this methodology for proposing most economic operating parameters.…”
Section: Application Of Rsm In Extraction Of Bioactive Compoundsmentioning
confidence: 93%